New York City Pop Financial Report 2023 (European journal of volunteering and community-based projects, 2024)
The paper highlights New York City's post-pandemic resilience while summarizing its budgetary situation for 2023. Despite persistent inequality, the 8.34 million-person city maintains its economic strength and diversity. Real estate taxes accounted for $110.3 billion of total receipts, while social services and education accounted for $106.8 billion of expenses. Sustainability, social justice, and public safety are important policy priorities. To ensure long-term stability, the city places a strong emphasis on budgeting and strategic investments.
Keywords: fiscal year 2023